Neonatal T Follicular Helper Cells Are Lodged in a Pre-T Follicular Helper Stage Favoring Innate Over Adaptive Germinal Center Responses - Mastelic-Gavillet, Beatris; Vono, Maria; Gonzalez-Dias, Patrícia; Ferreira, Frederico Moraes; Cardozo, Lucas; Lambert, Paul-Henri; Nakaya, Helder I.; Siegrist, Claire-Anne (Frontiers in Immunology, 2019)
T follicular helper (Tfh) cells have emerged as a critical limiting factor for controlling the magnitude of neonatal germinal center (GC) reactions and primary vaccine antibody responses. We compared the functional attributes of neonatal and adult Tfh cells at the transcriptomic level and demonstrated that the Tfh cell program is well initiated in neonates although the Tfh gene-expression pattern (i.e. CXCR5, IL-21, BCL6, TBK1, STAT4, ASCL2 and c-MAF) is largely underrepresented as compared to adult Tfh cells. Importantly, we identified a dominant TH2-bias of neonatal Tfh cells, with preferential differentiation toward short-lived pre-Tfh effector cells. Remarkably, adjuvantation with CpG-ODNs redirect neonatal pre-Tfh cells toward committed GC-Tfh cells, as illustrated by increased expression of Tfh signature genes and reduced expression of TH2-related genes.